Desarrollo de personajes antropomórficos con base en las características de la flora del parque Nacional Cotopaxi para la creación de un Artbook. - Cuaspa Sánchez, Daniela Estefanía (2019)
limited creation of graphic resources and the disinterest for similar projects, taking natural elements of the Cotopaxi National Park as influences, have been the main reason for this investigation. Letting the objective be a multidisciplinary study. Thanks to the use of the carried out research in the present project, it will be possible to have a sense of anthropomorphism applied to the illustration and the use of botanical scientific illustration to answer the question: How to characterize anthropomorphic characters through the creative illustration from the flora of the Cotopaxi National Park? This question is solved with the purpose of creating anthropomorphic characters inspired by the characteristics of Cotopaxi National Park flora through the use of ideas configuration, for its application in an art book. For which you can use the technical sheets to identify the existing flora in the park along with the photographic resource, in the same way, conversions and interviews with illustrators will be carried out that will contribute from its conception, the graphic style and elements influencers at the time of anthropomorphising characters, achieving the authors own style. For the illustration of characters the project methodology of Bruno Munari (1983) is used, as a point of reference for the process of development of the project, as well as the advancement of the creative process and the presentation of the final art through the adaptation of several methodologies and consolidated in one created by Cuaspa y Reyes (2018)